If x=t^3 and y=ln(1-t) what is dy/dx

Expert Answers

An illustration of the letter 'A' in a speech bubbles

You need to find t in terms of x and then you should substitute the expression in terms of x for t in equation `y = ln(1 - t)`  such that:

`x = t^3 =gt x^(1/3) = (t^3)^(1/3) =gt root(3) x = t`

`y = ln(1 - root(3) x)`

You need to find `(dy)/(dx), ` hence you need to use chain rule such that:

`(dy)/(dx) = ((1 - root(3) x)')/(1 - root(3) x)`

`(dy)/(dx) = -((1/3)*x^(1/3 - 1))/(1 - root(3) x)`

`(dy)/(dx) = -((1/3)*x^(-2/3))/(1 - root(3) x)`

`(dy)/(dx) = -1/(3*x^(2/3)*(1 - root(3) x))`

`(dy)/(dx) = -1/(3*root(3)(x^2)*(1 - root(3) x))`

Hence, evaluating `(dy)/(dx)`  under given conditions yields `(dy)/(dx) = -1/(3*root(3)(x^2)*(1 - root(3) x)).`

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial